Theologising migration : otherness and liminality in East Asia. - Woods, Paul (Fortress Press, 2015)
The Asian church has begun to respond and reach out to migrants. However, this concern for the other is patchy and lacks robust theological foundations. This work uses otherness and liminality as lenses to examine the Scriptures in order to understand God's heart for migrants and the responsibility of God's people toward them. It ends with some pointers toward concrete action by the church.